Corticosteroid suppression of antiviral immunity increases bacterial loads and mucus production in COPD exacerbations - Aran Singanayagam (Nature Portfolio, 2018)
Corticosteroid therapy is frequently used for chronic obstructive pulmonary disease (COPD) but its use is associated with increased risk of pneumonia. Here the authors show that corticosteroid use impairs innate and adaptive immunity to rhinovirus infection, which is restored by exogenous IFNβ.